Febuxostat may decrease the incidence of COVID-19 infection among patients with gout: a retrospective cohort study - Wang, Weijie; Wang, Shiow-Ing; Cheng, Yang; Wang, Xinchang; Fan, Yongsheng; Wei, James Cheng-Chung (Frontiers in Pharmacology, 2025)
BackgroundAs COVID-19 infection causes a kidney proximal tubule dysfunction with urinary loss of uric acid. Hypouricemia has been found in patients with severe COVID-19 disease. However, gout is a risk factor for COVID-19 incidence and COVID-19-related death. It is not known whether urate-lowering therapy could reduce the risk of infection of COVID-19 in gout patients or not.MethodsData from collaborative electronic health records were used in this study. A total of 663,729 patients with gout were enrolled between January 1, 2020 and December31, 2022 from 35,528,077 participants in US Collaborative Network with at least two visits. After exclusion and propensity score matching, 5,466 patients with Febuxostat and 5,466 patients with Allopurinol in the comparison group were selected. The hazard ratios (HRs) and 95% confidence intervals of COVID-19 incidence, and mechanical utilization were calculated between Febuxostat and Allopurinol groups. Subgroup analyses on sex, age, levels of serum uric acid, with vaccination group and sensitivity analyses for gout patients due to renal impairment or with tophus, different follow-up durations and considered competing risk were performed.ResultsCompared to Allopurinol group, Febuxostat significantly reduced the risk of COVID-19 incidence (HR = 0.878 [0.801–0.963]) and hospitalization (HR = 0.874 [0.772–0.989]). Febuxostat appears to be more effective in male, elder, without record of COVID-19 vaccination, and gout patients with serum uric acid<10 mg/dL in reducing the risk of COVID-19 infection. In addition, Febuxostat markedly reduced the hospitalization (HR = 0.652 [0.485–0.877]) in gout patients due to renal impairment or with tophus and the risks of COVID-19 incidence (HR = 0.878 [0.801–0.963]).ConclusionIn this retrospective cohort study, Febuxostat use was associated with a lower risk of COVID-19 among patients with gout for 3 years follow-up, even with renal impairment or tophus.